(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The importance of the current study was demonstrated by the possibility of addressing the administrative problems and obstacles that the Iraqi Sports League suffers from by introducing administrative approaches that enhance the position of its sports clubs at the strategic level, by providing an encouraging work climate to achieve sporting achievements, which in turn requires intensifying the marketing activities supporting them, which work to Sustaining its success in the Iraqi environment and launching regionally and then globally . The study aimed to test the mediating role of the work life quality (WLQ) in enhancing the relationship between marketing ambidexterity (MA) and the strategic niche (SN) of Iraqi sports clubs. The Ministry of Youth and Sports was chosen as an applied field for the study, by distributing a questionnaire that included (300) respondents from the administrative, scientific, and training leaders of the directorates affiliated with the Ministry, as well as About the boards of directors of Iraqi sports clubs. A five-point Laser scale was used, and in order to conduct descriptive and analytical tests of the respondents’ data, the programs (SPSS, AMOS) and the (Sobel) test were relied upon to ensure the significance of the mediation of the work life quality. One of the most important results reached is the presence of an effective mediating role for the work life quality in enhancing the relationship between marketing Ambidexterity and strategic niche, according to the study sample’s point of view. One of the most important conclusions reached is that adopting the marketing ambidexterity approach has an effective impact on enhancing the strategic niche of the sports clubs in the study sample in light of the growing competition in the Iraqi sports sector, and therefore there is a need to employ the mediating role of the work life quality in enhancing the positive relationship between marketing ambidexterity and strategic niche, in line with providing new training services and consultations that add value to these clubs.